Can Malaysia Move to Tier 1? Analysing the Current Trends and Case Studies of Human Trafficking - Ilham Hussin, Nafisah; Othman, Zarina; Mohd Hed, Norhafiza; Mohd Azmi, Nadirah (JSP (Jurnal Ilmu Sosial dan ilmu Poltik), 2025)
This study explores Malaysia’s persistent challenges in advancing to Tier 1 in the US Trafficking in Persons (TIP) Report, highlighting systemic barriers such as weak enforcement, corruption, and insufficient victim protection. Despite existing anti-trafficking laws, poor implementation and limited support services have hindered efforts to combat human trafficking. The study examines key sectors vulnerable to trafficking—including palm oil plantations, manufacturing, and domestic labour—to identify critical gaps that perpetuate exploitation and abuse. A comparative analysis with the Philippines, an ASEAN country ranked at Tier 1, provides insights into successful strategies that Malaysia could adopt. The Philippines has implemented specialised anti-trafficking courts, victim-centred programs, and comprehensive enforcement mechanisms, contributing to its progress in addressing human trafficking. Malaysia, by contrast, has struggled with inconsistent prosecutions and inadequate rehabilitation services for victims, which have negatively impacted its TIP ranking. The findings suggest Malaysia must adopt a multi-dimensional approach to improve its anti-trafficking efforts. Key recommendations include strengthening legal frameworks, enhancing victim protection services, increasing prosecution rates, and fostering regional partnerships. Addressing these systemic challenges is crucial for safeguarding vulnerable populations, improving Malaysia’s international reputation, and promoting justice and human rights. Achieving Tier 1 status would signify a major step forward in Malaysia’s commitment to combating trafficking and ensuring accountability for perpetrators.